Новый вид совки из Северного Приамурья (Lepidoptera, Noctuidae) - Свиридов, А.В. (Вестник зоологии, 1984)
Xestia selendzhinka Sviridov, sp. n.- similar to X. tecta Hb., differs in narrower, elongated fore- and hindwing, dark-brown colour and some minor wing-pattern peculiarities. Type-material: holotype ♀, Amur distr., Selemdzhinsk, 30.08.1976, A. Sviridov leg. (deposited in Zoological Museum, Moscow State University).